Analysis of Text Books of Early Islamic Education in Primary Schools (Published by Erlangga and Yudhistira) - Nurzannah Nurzannah; Juli Maini Sitepu (Proceeding International Seminar of Islamic Studies, 2019)
The purpose of this study was to determine the quality of the contents of Islamic religious education (PAI) grade I and II elementary schools published by Erlangga and Yudhistira, related; conformity with curriculum, concept truth, language truth, truth Illustration / media and language / sentence suitability with the age of Early Childhood. The research method used is descriptive qualitative, using two approaches, namely; text approach and context approach. In addition, the content analysis method is also used. The results showed that: The contents of the four books are in accordance with the curriculum containing KI 1, KI 2, KI 3, and KI 4. The text and sentences used did not meet the standard rules of Indonesian grammar, the sentences presented were very few using punctuation like; capital letters are not used significantly, (this is found in class I books while class II books are in accordance with Indonesian rules). Illustration / media is quite adequate and very coloring pages by pages of books, both for classes I and II. However, when confirmed between statements or orders, or questions, and illustrations made, it is not appropriate. The use of language and sentences, for grade I books, does not address the age aspects of children. Where, the sentences used are too long, many use words that are classified as high for elementary school age children in grade I. while grade II can be said to be standard. The use of Arabic sentences will not be able to be read by children, if they are not fluent in reading the Koran.